(untitled) (Revista Cientifica Ingenio Magno, 2022)
Abstract — During July of 2016 and June of 2017 a crop of 200 plants of lemongrass (Cymbopogon citratus) were planted in the Picón Arenal district of the municipality of Yopal. During the whole cycle, 3 cuts of the leaf were made for its distillation and extraction of essential oil. A yield of 0.004 P/P was found in the first cut, 0.003 P/P in the second and 0.002 P/P in the third. Through gas chromatography coupled to mass spectrometry, 31 compounds were determined, the main ones were citral, then β-myrcene, among others with a percentage between 6% and lower than 2%. The essential oil extracted with this crop under the environmental conditions present in the municipality of Yopal, showed less composition of citral, main compound reported in other parts of the world, however, its high percentage of myrcene attributes other medicinal properties of equal commercial interest in the pharmaceutical industry.